Toxicological effects of regulated mycotoxins and persistent organochloride pesticides: In vitro cytotoxic assessment of single and defined mixtures on MA-10 murine Leydig cell line. (April 2018) - Eze, Ukpai A.; Huntriss, John; Routledge, Michael N.; Gong, Yun Yun
Abstract: Epidemiological studies show that there is global decline in male fertility primarily as a result of poor sperm quality and this is attributed to exposure to endocrine disrupting chemicals (EDCs) in the environment, food and pharmaceutical products, including mycotoxins and pesticides. The Leydig cells in the male testes are responsible for producing androgens, hormones that play major roles in male development and reproductive function. Therefore, any toxin that affects the function and morphology of the Leydig cells may result in sub-fertility or infertility. The cytotoxic effects of single and binary mixtures of aflatoxin B1 (AFB1 ), ochratoxin A (OTA), deoxynivalenol (DON), zearalenone (ZEN), alpha-zearalenol (α-ZOL), beta-zearalenol (β-ZOL), 1, 1, 1-trichloro-2, 2-bis( p -chlorophenyl) ethane ( p, p ′-DDT) and 1, 1-dichloro-2, 2-bis( p -chlorophenyl) ethylene ( p, p ′-DDE) on a model cell line, the MA-10 Leydig cells, were evaluated using 3-[4, 5-dimethylthiazol-2-yl]-2, 5-dipenyltetrazolium bromide (MTT) assay after 48 h of exposure. With single toxin treatment at doses between 0.1 μM and 64 μM for 48 h, DON was the most cytotoxic to MA-10 cells with a half maximal inhibitory concentration (IC50 ) value of 12.3 μM followed by α-ZOL (IC50 : 28 μM) and OTA (IC50 : 30 μM) while the IC50 of AFB1, p, p ′-DDT and p, p ′-DDE were above the highest concentration tested (64 μM). Co-exposure with p, p ′-DDT or p, p ′-DDE enhanced the toxicity of DON, OTA and ZEN to MA-10 Leydig cells, particularly at higher concentrations. This highlights the possible adverse effects on male reproductive health following co-exposure to these toxins. Highlights: We examined the effects of single and binary mixtures of mycotoxins and pesticides. Deoxynivalenol was the most cytotoxic to MA-10 Leydig cells (IC50 : 12.3 μM). Zearalenone and its metabolites at a dose of 16 μM stimulated cell proliferation. Aflatoxin B1 reduced the cytotoxic effects of deoxynivalenol. The toxicity of deoxynivalenol, ochratoxin A and zearalenone is enhanced by pesticides.